Prevalence of Vesiculobullous Lesions: A Hospital Based Retrospective Study - Pranati T1 , Manjari Chaudhary2 , Adimulapu Hima Sandeep3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Vesiculobullous lesions, characterized as mucocutaneous, have a significant impact on quality of life whencompared to other conditions, as they can lead to pain and difficulty in eating and speech, depending on theextent of the ulceration. The overlapping pattern of clinical presentation of vesiculobullous lesions in theoral mucous membranes makes it difficult for the clinicians to arrive at a proper diagnosis. Hence carefulevaluation of clinical, histological and immunofluorescence data aids the clinician to arrive at a properdiagnosis. The aim of this study is determine the prevalence, age and gender variations of vesiculobullouslesions pertaining to oral mucosa among patients who have visited Saveetha Dental College, Chennai, India.A retrospective study was conducted and data collection was done from dental archives pertaining from June2019 to April 2020. Data consisted of details of patients who presented with vesiculobullous lesions of theoral mucosa. Data was imported to IBM SPSS Version 20 for statistical analysis. Results were tabulated.Prevalence of vesiculobullous lesions pertaining to the oral cavity was more in females (51.8%) comparedto males. (42.8%). Prevalence was more in patients belonging to the fourth decade of life (30.1%). Herpeslabialis was found to be more prevalent among the vesiculobullous lesions seen in the oral cavity. Lesionswere present in both the arch (44.6%) followed by lesions pertaining to only upper arch. Associations in thisstudy were not statistically significant (p>0.05). The association between age and gender shows prevalenceof herpes labialis to be the highest among all the age groups. There are very minimal studies done on theprevalence of vesiculobullous lesions pertaining to the oral cavity. In this study it has been found thatvesiculobullous lesions of infectious origin (Herpes labialis) were found to be more prevalent compared tovesiculobullous lesions of autoimmune origin. This study was conducted in a single centre. Extensive multicentre study is to be done.